Novel Treatment of Disseminated Coccidioidomycosis in a Dog with Voriconazole - Raghu, Chantel (Case Rep Vet Med, 2018)
A dog with disseminated coccidioidomycosis involving the vertebral, cutaneous, and pulmonary systems was treated successfully with voriconazole after failing traditional therapy with fluconazole and terbinafine. This report is the first to describe the successful management of refractory coccidioidomycosis with voriconazole in a dog.